Crooked house [videorecording (DVD)] - Christie, Agatha, 1890-1976; Paquet-Brenner, Gilles; Irons, Max, 1985-; Martini, Stefanie, 1990-; Close, Glenn, 1947- (Sony Pictures Home Entertainment, 2018)
In Agatha Christie's most twisted tale, a spy-turned-private-detective is lured by his former lover to catch her grandfather's murderer before Scotland Yard exposes dark family secrets.